Serial Intravesical Pressure Measurements Can Predict the Presence and the Severity of Necrotizing Enterocolitis - Tanriverdi, Sema; Koroglu, Ozge; Uygur, Ozgun; Celik, Ahmet; Dulger, Fatma; Yalaz, Mehmet; Akisu, Mete; Kultursay, Nilgun (European Journal of Pediatric Surgery, 2013)
Background and Aims Necrotizing enterocolitis (NEC) which is accompanied with gastrointestinal ulceration and necrosis is one of the most important problems of preterm infants in neonatal intensive care unit (NICU). Increased intra-abdominal pressure (IAP) is detected among most of the pediatric patients hospitalized in intensive care unit and undergoing surgery or trauma. This pathology, namely, abdominal compartment syndrome, causes ischemia and hypoperfusion of abdominal organs. Recently, the effect of increased IAP on NEC is under focus and this increase is thought to be related with the onset of NEC by leading to intestinal ischemia and necrosis. In this study, we aimed to investigate if serial intravesical pressure (IVP) measurements as an indirect indicator of IAP may help to early diagnosis in NEC and to decision for surgery besides to predict the mortality of NEC.Material and Method A total number of 61 preterm infants with a birth weight of ≤ 1,500 g hospitalized in NICU were included to the study. IVP values were measured by the same nurse twice daily during their hospitalization through urinary catheter. The IVP values of the preterm infants with and without NEC were compared.Results Totally 61 premature infants included in the study were grouped as follows: group 0, the control group without NEC (n = 38); group 1, medically treated NEC patients (n = 14); and group 2, NEC patients undergoing surgery (n = 9). The median IVP measurements of group 0 were lower than the other groups (p = 0.001). No statistically significant difference in IVP measurements was detected between group 1 and group 2 (p = 0.155). A 10% of increase in IVP measurement was significant in predicting the development of NEC with consecutive serial measurements. The mean IVP measurements were higher in infants with NEC who died during their follow-up at NICU compared with NEC patients who survived (p = 0.043).Conclusion Serial IVP measurements may help for early diagnosis and surgery decision of NEC and high IVP levels also may predict mortality in cases with NEC.
Keywords: necrotizing enterocolitis; intra-abdominal pressure; intravesical pressure; newborn